Fish consumption and breast cancer risk. The European Prospective Investigation into Cancer and Nutrition (EPIC). - Engeset, D; Alsaker, E; Lund, E; Welch, A; Khaw, K; Clavel-Chapelon, F; Thiébaut, A; Chajès, V; Key, T; Allen, N; Amiano, P; Dorronsoro, M; et al. (2006)
There is current interest in fish consumption and marine omega-3 (n-3) fatty acids and breast cancer risk. Some in vitro and animal studies have suggested an inhibitory effect of marine n-3 fatty acids on breast cancer growth, but the results from epidemiological studies that have examined the association between fish consumption and breast cancer risk in humans are inconsistent. We examined fish consumption and breast cancer risk in 310,671 women aged between 25 and 70 yr at recruitment into the European Prospective Investigation Into Cancer and Nutrition (EPIC). The participants completed a dietary questionnaire between 1992-98 and were followed up for incidence of breast cancer for a median of 6.4 yr. Hazard ratio for breast cancer by intake of total and lean and fatty fish were estimated, stratified by study centre and adjusted for established breast cancer risk factors. During follow-up, 4,776 invasive incident breast cancers were reported. No significant associations between intake of total fish and breast cancer risk were observed, hazard ratio (HR) 1.01 (95% confidence interval [CI] 0.99-1.02; p = 0.28 per 10 g fish/day). When examining lean and fatty fish separately, we found a positive significant association only in the highest quintile for fatty fish (HR 1.13, 95% CI 1.01-1.26), but test for trend was not significant (p = 0.10). No associations with breast cancer risk were observed when the study participants were subdivided by menopausal status. Although the period of follow-up is relatively short, the results provide no evidence for an association between fish intake and breast cancer risk.